Effects of an eHealth Intervention on Patient-Provider Interaction and Functional Health Literacy in Adults With Hypertension - Ronald L. Hickman Jr., PhD, RN, ACNP-BC, FNAP, FAAN; John M. Clochesy PhD, RN, FCCM, FAAN; Marym Alaamri PhD, RN (SAGE Publishing, 2021)
Introduction Hypertension is a life-limiting, chronic condition affecting millions of Americans. Modifiable factors, quality of the patient-provider interaction and functional health literacy, have been linked to effective hypertension self-management. However, there has been limited interventional research targeting these modifiable factors. Electronic hypertension self-management interventions, in particular those incorporating virtual simulation, may positively influence the quality of the patient-provider interaction and functional health literacy status of adults with hypertension. Yet there is a dearth of evidence examining the efficacy of eHealth interventions targeting these modifiable factors of hypertension self-management. Objective Evaluate the effects of two electronic hypertension self-management interventions on the quality of the patient-provider interaction and functional health literacy in adults with hypertension. Methods A convenience sample of community-dwelling adults (>18 years) with hypertension were recruited and randomized to an avatar-based simulation (eSMART-HTN) or a video presentation on hypertension self-management (attention control). Participants were administered questionnaires to capture demographic characteristics, the quality of the patient-provider interaction, and functional health literacy. Questionnaire data were collected at baseline, and then monthly across three months. Two separate repeated measures analysis of covariance models were conducted to assess the effects of the interventions across the time points. Results The sample included 109 participants who were predominately middle-aged and older, nonwhite, and female. Scores for the quality of the patient-provider interaction demonstrated significant within-group changes across time. However, there were no significant differences in the quality of the patient-provider interaction or functional health literacy scores between experimental conditions while adjusting for covariates. Conclusion An avatar-based simulation (eSMART-HTN) intervention proved to have a positive effect on patient-provider interaction compared to an attention control condition. Although the results are promising, future research is needed to optimize the effectiveness of eSMART-HTN and enhance its efficacy and scalability in a larger cohort of adults with hypertension.